Ação de pesticidas em Metarhizium anisopliae no solo - Mochi, Dinalva A. [UNESP]; Monteiro, Antonio C. [UNESP]; Barbosa, José C. [UNESP] (Springer Nature, 2005)
The present study aimed to analyze the action of some acaricides, fungicides, insecticides and herbicides containing different active ingredients on Metarhizium anisopliae Metsch. (Sorokin) inoculated into autoclaved soil. The action of the pesticides was evaluated based on the fungal respiratory activity. The first assessment was done at 48h after inoculation. The pesticides were then added and respiratory activity was determined nine times every 48h and an additional five times every 4 days. Except for the fungicides, no significant effect (P > 0.05) of the pesticides on M. anisopliae was observed. A reduction in CO2 production was observed for the mancozeb treatment from day 4 to day 6 of incubation, and for tebuconazol between days 4 and 6, 8 and 10, and 32 and 36. The same was observed for copper oxychloride between days 10 and 12 and 32 and 36, and for chlorothalonyl between 8 and 10, 10 and 12, and 32 and 36 days of incubation. Identical effect occurred for the acaricides abamectin and fenbutatin oxide, with a reduction in CO2 production between 20 and 24 days of incubation. The herbicides glyphosate, trifluralin and ametrin reduced the respiratory activity of the fungus between days 10 and 12, while the insecticide trichlorfon reduced respiratory activity only from 32 to 40 days of incubation. The results indicate that the toxic action of pesticides on the fungus in soil is small, suggesting that this pest control bioagent can be used in combination with pesticides without compromising its activity.
Action of pesticides to Metarhizium anisopliae in soil
Keywords: Biological control; Entomopathogenic fungus; Integrated management; Respiratory activity; Fungi; Metarhizium anisopliae